Scientific Opinion on the safety and suitability for use by infants of follow‐on formulae with a protein content of at least 1.6 g/100 kcal. (11th May 2017) - ,; Turck, Dominique; Bresson, Jean‐Louis; Burlingame, Barbara; Dean, Tara; Fairweather‐Tait, Susan; Heinonen, Marina; Hirsch‐Ernst, Karen Ildico; Mangelsdorf, Inge; McArdle, Harry J; Naska, Androniki; Neuhäuser‐Berthold, Monika; et al.
Abstract: Following a request from the European Commission, the EFSA Panel on Dietetic Products, Nutrition and Allergies (NDA) was asked to deliver a scientific opinion on the safety and suitability for use by infants of follow‐on formulae (FOF) based on cow's milk intact protein with a protein content of at least 1.6 g/100 kcal (rounded value) that meet otherwise the requirements of relevant EU legislation. If the formula under evaluation is considered to be safe and suitable for use by infants, the NDA Panel is also asked to advise on whether FOF based on goat's milk intact protein, soy protein isolates or protein hydrolysates are also safe and suitable for infants under the same conditions. The Panel concludes that the use of FOF with a protein content of at least 1.6 g/100 kcal from either intact cow's milk protein or intact goat's milk protein otherwise complying with the requirements of relevant EU legislation is safe and suitable for healthy infants living in Europe with an intake of complementary foods of a sufficient quality. This conclusion does not apply to infant formula (IF). The Panel also concludes that the safety and suitability of FOF with a protein content of at least 1.6 g/100 kcal manufactured from either protein hydrolysates or soy protein isolates cannot be established with the available data. The same conclusion applies to IF. The NDA Panel endorsed a draft of this scientific opinion on 14 December 2016 for public consultation. The draft document has been revised and updated according to the comments received, where appropriate. Abstract : This publication is linked to the following EFSA Supporting Publications article: http://onlinelibrary.wiley.com/doi/10.2903/sp.efsa.2017.EN-1215/full